Pengaruh Kegiatan Finger Painting Terhadap Perkembangan Motorik Halus Anak Usia Pra Sekolah di TK Tunas Kelapa Kelompok B Desa Tinigi Kecamatan Galang - Katrina Feby Lestari; Norma Onggang; Ni Nyoman Udiani (Jurnal Rumpun Ilmu Kesehatan, 2021)
Around 40% there are still children of pre-school age who have not been able to do their developmental tasks according to their age. In addition, in the kindergarten, finger painting activities have never been done on the soft motor development of pre-school children in Tunas Kelapa Kindergarten Group B Tinigi Village, Galang District. This type of quantitative research with a one group pretest posttest approach, a population of 32 people and a sample of 15 people with purposive sampling technique. Data analysis used the Wilcoxon test, with finger painting as an independent variable and fine motor dependent. The results of the pretest study were 8 respondents (53.3%) suspect and the posttest was 13 respondents (86.7%) normal. The results of bivariate analysis obtained p value 0.014 <0.05, there is an effect of finger painting activities on the soft motor development of pre-school children in Tunas Kelapa Kindergarten Group B Tinigi Village, Galang District. It is hoped that this research can be additional knowledge for parents so they can optimize the development of their children.